Current lipid-lowering approach and LDL target achievement in very high-risk patients: in-hospital results of a high-volume primary percutaneous coronary intervention tertiary center. (11th May 2022) - Ciatti, F; Di Muro, FM; Mattesini, A; Ristalli, F; Stolcova, M; Meucci, F; Di Mario, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Low-density lipoprotein-cholesterol (LDL-C) is a well-accepted causal risk factor for atherothrombotic cardiovascular disease. Several randomized controlled trials and meta-analyses have shown that lipid-lowering therapies reduce cardiovascular events and have a positive effect in reducing vulnerable plaques. In particular, the recommended target for LDL-C has become more and more stringent, moving to 1.4 mmol/l (55 mg/dl) for very high-risk patients. According to the 2019 ESC/EAS Guidelines, the current paradigm for lipid management favors a stepwise approach consisting of early initiation of high-intensity statin, followed by subsequent addition of ezetimibe, and ultimately a consideration of PCSK9 inhibitor treatment if LDL-C levels remain elevated. Methods: We recruited 307 patients admitted for acute coronary syndrome (ACS) during the COVID-19 pandemic from March 2020 to December 2020. Baseline LDL-C concentration and prescribed hypolipemiant treatment at hospital admission and discharge were registered. Therefore, we included all consecutive patients identified as very-high cardiovascular risk, according to 2019 ESC guidelines. We stratified our population through variables independently associated with non-attainment of LDL-cholesterol such as hypertension, diabetes, peripheral arterial disease, clinical manifestations of ACS, number of main vessels treated, and complexity of the atherosclerotic disease. Results: 274 patients were included. Mean age was 69, 9 years (SD 11, 4), 20, 8 % were women, 23, 7 % had diabetes, 16, 4 % had PAD and 32, 1 % suffered from valvular disease, mainly with mitral regurgitation or aortic stenosis no more than mild or moderate. Of 25.1% with a previous history of acute myocardial infarction, the 33, 3% of whom didn't have statin therapy pre-ACS index (p =0, 001). At admission, medium cholesterol levels of patients that underwent previous coronary revascularization (25, 5% of the total population) were 84, 21 ± 31, 2 mg/dL, not in range according to both 2016 and 2019 ESC guidelines. At discharge, 77, 37 % of all the patients included received only statin therapy VS 22, 63% with statin plus ezetimibe. In the subpopulation of patients with recurring ACS events with LDL pre-admission > 100 mg/dL, despite high dose statin, only 25% of this population were discharged adding ezetimibe (VS 75% who kept on the treatment of high dose statin without up-titration). Conclusions: Management of dyslipidemia is frequently suboptimal and the gap between guidelines and clinical practice for lipid management across Europe has been exacerbated by the 2019 guidelines. A greater utilization of non-statin lipid-lowering therapies is likely needed to reach the LDL-C optimal target. A correct stratification of the risk class would help to identify, in a personalized perspective of treatment, patients at very high risk that would take advantage of more aggressive therapy to reach the lowest target of LDL-C ("the lower is better").